Avaliação da migração de metais e outros elementos provenientes de frigideiras para simulantes aquosos ácidos e gordurosos - Tascheto, Leticia (My University, 2025)
The interaction between cooking utensils and food can be either beneficial or harmful to health, making studies essential to ensure safe levels of exposure to potentially toxic elements. The materials used in the production of these utensils include stainless steel, aluminum, and cast iron, as well as surfaces coated with polymers such as polytetrafluoroethylene (PTFE) or ceramic coatings. In this context, the main objective of this study was to evaluate the interaction of frying pans made from these materials with acidic and fatty food simulants, aiming to verify compliance with national regulations and make comparisons between the different types of samples analyzed. For this, characterization and chemical analysis techniques were employed to determine the composition of the frying pans and quantify the elements that could migrate from these samples into food simulants after exposure tests. The study also analyzed the influence of frying pan wear on the migration of elements into these simulants. Overall, the results showed that all the frying pans analyzed complied with the migration limits established by Brazilian regulations, according to the criteria set by the Health Surveillance Agency. In the comparative tests, none of the samples exhibited total migration above the detection limit of the method (21.89 mg/kg), either before or after wear. Regarding specific migration tests, the following elements were identified: (i) Al, Cu, Cr, and Fe in the stainless steel frying pan, with Fe showing the highest migration (1.96 mg/kg of simulant); (ii) Al, Cd, Cu, Fe, and Mn in the aluminum frying pan, with Al being the element of highest migration (26.8 mg/kg of simulant); (iii) Al, Cd, Pb, Cu, Cr, Sn, Fe, and Mn in the cast iron frying pan, with Fe being the element with the highest migration (6157.61 mg/kg of simulant); (iv) Al, Cd, Pb, Cu, and Fe in the aluminum frying pan with PTFE polymer coating, with Al predominating (1.46 mg/kg of simulant); and (v) Al, Cd, Cu, Fe, and Mn in the aluminum frying pan with ceramic coating, with Al being the element with the highest migration (2.12 mg/kg of simulant). In conclusion, it was possible to verify that studies of this nature are essential for defining safe limits for daily exposure to potentially toxic elements, contributing to the mitigation of health risks and the improvement of regulatory criteria for utensils intended for contact with food. [resumo fornecido pelo autor]
A interação entre utensílios culinários e alimentos pode ser benéfica ou prejudicial à saúde, tornando indispensáveis estudos para garantir níveis seguros de exposição a elementos potencialmente tóxicos. Entre os materiais utilizados na fabricação desses utensílios estão o aço inoxidável, alumínio e ferro fundido, além de superfícies revestidas com polímeros, como o poli(tetrafluoroetileno) (PTFE), ou revestimentos cerâmicos. Nesse contexto, este trabalho teve por objetivo principal avaliar a interação de frigideiras confeccionadas com essas matérias-primas com simulantes de alimentos ácidos e gordurosos, com o intuito de verificar a conformidade com as exigências das legislações nacionais e realizar comparações entre os diferentes tipos de amostras analisadas. Para tanto, foram empregadas técnicas de caracterização e análise química, a fim de verificar a composição das frigideiras e quantificar os elementos que eventualmente poderiam migrar dessas amostras para simulantes alimentares, após testes de exposição. O estudo também analisou a influência do desgaste das frigideiras na migração de elementos para esses simulantes. De maneira geral, os resultados mostraram que todas as frigideiras analisadas atenderam aos limites de migração estabelecidos pela regulamentação brasileira, conforme os critérios da Agência de Vigilância Sanitária. Nos ensaios comparativos, nenhuma das amostras apresentou migração total acima do limite de detecção do método (21,89 mg/kg), antes ou após o desgaste. Em relação aos ensaios de migração específica, foram identificados os seguintes elementos: (i) Al, Cu, Cr e Fe na frigideira de aço inoxidável, com Fe apresentando a maior migração (1,96 mg/kg de simulante); (ii) Al, Cd, Cu, Fe e Mn na frigideira de alumínio, destacando-se Al, cuja migração alcançou 26,8 mg/kg de simulante; (iii) Al, Cd, Pb, Cu, Cr, Sn, Fe e Mn na frigideira de ferro fundido, sendo Fe o elemento de maior migração (6157,61 mg/kg de simulante); (iv) Al, Cd, Pb, Cu e Fe na frigideira de alumínio com revestimento polimérico de PTFE, com predominância de Al, (1,46 mg/kg de simulante); e (v) Al, Cd, Cu, Fe e Mn na frigideira de alumínio com revestimento cerâmico, sendo Al o elemento com maior migração (2,12 mg/kg de simulante). Como conclusão, foi possível verificar que estudos dessa natureza são essenciais para definir limites seguros de exposição diária a elementos potencialmente tóxicos, contribuindo para a mitigação de riscos à saúde pública e o aprimoramento dos critérios regulatórios aplicáveis a utensílios destinados ao contato com alimentos. [resumo fornecido pelo autor]
Keywords: Materiais - Testes; Utensílios domésticos; Substâncias tóxicas; Ciência dos materiais; Materials - Testing; House furnishings; Toxic substances; Materials science